Who’s Afraid of Seneca? Conflict And Pathos in the Romantic-Idealistic Theory of Tragedy - Pinna, Giovanna (Aesthetica Preprint, 2021)
This paper reconsiders the Idealistic aesthetics of tragedy from an unconventional point of view. It investigates the relationship between theory and dramatic canon by focusing on those works and authors that are excluded from the canon by the theoretical discourse. My aim is to show that Idealist philosophers and Romantic critics concur in constructing a unitary model of the tragic conflict that is partly defined through its contraposition to the ‘Senecan’ conception of tragedy as a representation of suffering and as a dialectic of passions. Seneca here stands for an entire line of European dramaturgy, culminating in French Classicism, in which the negativity that produces the mournful outcome is rooted in the inner self of the tragic hero and is not redeemed by the affirmation of a superior ethical or metaphysical instance. This contrast does not merely concern a literary model, but also, more generally, the conception of subjectivity underlying the dramaturgy of passions. This paper thus helps to shed light on the controversial relationship between the idealistic philosophy of the tragic with modern tragedy at large.